If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + -1 = 5p + 3p + -8 Reorder the terms: -1 + p = 5p + 3p + -8 Reorder the terms: -1 + p = -8 + 5p + 3p Combine like terms: 5p + 3p = 8p -1 + p = -8 + 8p Solving -1 + p = -8 + 8p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-8p' to each side of the equation. -1 + p + -8p = -8 + 8p + -8p Combine like terms: p + -8p = -7p -1 + -7p = -8 + 8p + -8p Combine like terms: 8p + -8p = 0 -1 + -7p = -8 + 0 -1 + -7p = -8 Add '1' to each side of the equation. -1 + 1 + -7p = -8 + 1 Combine like terms: -1 + 1 = 0 0 + -7p = -8 + 1 -7p = -8 + 1 Combine like terms: -8 + 1 = -7 -7p = -7 Divide each side by '-7'. p = 1 Simplifying p = 1
| 32/5-11/4 | | 3c+8c=55 | | 30-3x=18 | | -(2n-1)-3(n+2)=7 | | -60-9x=124-31x | | x^2-6+24=0 | | 4(2a-8)=(1/7)(49a+70) | | 1=2r | | -7/3x=-6 | | 4(5x-4)+2(19-2x)-5(3x+5)=-13 | | 3w+7y+7x+8x-14y+5w= | | (6y+5)-(3+5y)=7 | | 2x(x-4)=-6 | | 4p+9q=45 | | X+9=6+6x | | 0=5x-20x^3+16x^5 | | x^2-6=7x+12 | | 5x+3=6x+5 | | 8p+8=7p+12 | | -3(3b+2)+(10b-4)=0 | | x/5+3=-6 | | 13x+90= | | x+16.84=8.84 | | 0=x(5-20x^2+16x^4) | | x-16.84=8.84 | | x-8.84=16.84 | | an=5+6 | | 3/7x+5 | | 7(4x+1)=231 | | 0.11x=0.88 | | 1/2(x-9)=2x-4 | | 12(4+d)= |